Thermal history and differential exhumation across the Eastern Musgrave Province, South Australia: Insights from low-temperature thermochronology - Glorie, S.; Agostino, K.; Dutch, R.; Pawley, M.; Hall, J.; Danisik, Martin; Evans, Noreen; Collins, A. (Elsevier BV, 2017)
© 2017 Elsevier B.V.Multi–method geo- and thermochronological data obtained for Palaeo- and Mesoproterozoic granitoids traversing the main structural architecture of the eastern Musgrave Province within South Australia reveal multiphase cooling histories. Apatite U-Pb dating on six samples yield consistent ages of ~ 1075–1025 Ma, suggesting a thermal reset coinciding with mantle-derived magmatism of the greater Warakurna Large Igneous Province (~ 1080–1040 Ma). Apatite fission track (AFT) analysis indicate that four discrete thermal events affected the study area, inducing cooling through the AFT partial annealing zone (~ 60–120 °C), supported by apatite and zircon (U-Th-Sm)/He data. Late Neoproterozoic cooling from deep crustal levels to temperatures < 200 °C was discerned, which is thought to be related to exhumation and denudation during the Petermann Orogeny. Subsequent cooling events at ~ 450–400 Ma (Silurian–Devonian) and ~ 310–290 Ma (Late Carboniferous) are interpreted to represent exhumation associated with the Alice Springs Orogeny. The latter event exhumed the sampled plutons to shallow crustal depths. An additional Triassic – early Jurassic thermal event, likely recording elevated geothermal gradients at that time, was observed throughout the study area, however, more data is needed to further support this interpretation. The high sample density across the structural architecture of the study area furthermore reveals patterns of fault reactivation and resulting differential exhumation, indicating shallower exhumation levels in the centre and deeper exhumation towards the margins of the sampled transect. The observed differential exhumation patterns match with existing seismic data and fit a model of an inverted graben system for the Phanerozoic evolution of the eastern Musgraves. The results highlight a complex Phanerozoic thermal history for the eastern Musgraves and help to elucidate the poorly appreciated tectonic evolution of inland Australia. This study further demonstrates how high-density sample transects across structural architecture can assess the relative crustal level and associated preservation of the thermal history record within fault-reactivated terranes.